2021
DOI: 10.26905/jkdp.v25i3.5758
|View full text |Cite
|
Sign up to set email alerts
|

Diversification Strategy and Good Governance: Does It Affect Firm’s Leverage?

Abstract: This paper aims to analyze whether firm diversification affects firm leverage in developing countries. This research model is based on the agency theory view that focuses on diversification in leverage through good governance mechanisms. The data comes from 43 companies from 215 observation companies listed on the Indonesia Stock Exchange in the 2014–2018 period, supporting the co-insurance hypothesis; our findings suggest a positive effect of diversification on debt levels. Our findings show that cost advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
2
1
Order By: Relevance
“…This conclusion is not consistent with the work of Agrawal and Mandelker (1987), Hill and Snell (1988), Johnson et al (1993), andDenis et al (1997). Nahda and Rahmadana (2021) showed that cost advantages occur in diversified firms, including higher debt ratios in the firm's capital structure. The participation of the manager has a negative and significant effect on the growth of the main activity this result confirms the study conducted by Morck et al (1988) and Jensen and Ruback (1983), which suggested that the participation of the manager is negatively related to the strategic choice of the company and positively to the growth of the main activity.…”
Section: Results Of Estimates and Interpretationscontrasting
confidence: 68%
“…This conclusion is not consistent with the work of Agrawal and Mandelker (1987), Hill and Snell (1988), Johnson et al (1993), andDenis et al (1997). Nahda and Rahmadana (2021) showed that cost advantages occur in diversified firms, including higher debt ratios in the firm's capital structure. The participation of the manager has a negative and significant effect on the growth of the main activity this result confirms the study conducted by Morck et al (1988) and Jensen and Ruback (1983), which suggested that the participation of the manager is negatively related to the strategic choice of the company and positively to the growth of the main activity.…”
Section: Results Of Estimates and Interpretationscontrasting
confidence: 68%
“…Diversification of insurance products (product diversified -PD) is measured by the Herfindahl Index (Wu & Deng, 2021); (Foong & Idris, 2012); (Nahda & Rahmadana, 2021). Pi is the total premium of the product line divided by the total premium of the insurance company, n symbolizes the number of product lines.…”
Section: Leverage = Total Liabilities Total Equitymentioning
confidence: 99%
“…An emerging market firm involve to has a higher proportion of diversification costs since the product's issues are changing faster (Nwakoby & Ihediwa, 2018). However, the resulting study by (Nahda & Rahmadana, 2021) states that there is a positive relationship between diversification and leverage, indicating higher power for a more diversified company.…”
mentioning
confidence: 99%